Consumer payment behavior by income and demographics - Claire Greene; Julian Perry; Joanna Stavins (Federal Reserve Bank of Boston, 2024)
Despite the introduction of an array of innovations and new payment options for consumers over the last decade, income and demographics remain significant predictors of payment behavior. Using data from a 2023 consumer payments diary, we find that income, age, and education are significant predictors of which payment instruments consumers adopt and use. These associations hold not only for traditional payment instruments-cards and paper-but also for innovations such as mobile apps; buy now, pay later (BNPL); and cryptocurrency. In 2023, less educated consumers were significantly less likely than other consumers to adopt any payment instrument, especially checks and electronic payments, even when we control for income and employment. After controlling for education, we find that high-income consumers used credit cards significantly more relative to other consumers. Younger and more educated consumers were most likely to adopt mobile payment apps. Women, Black and Latino consumers, and those who had filed for bankruptcy in the previous year were significantly more likely to have used BNPL. Men were nearly three times as likely as women to adopt cryptocurrency.
Keywords: E41; D14; D12; 330; payment instruments; consumer payments; payment behavior